Beginning of military nursing in the Spanish military aviation - Jaime E. Saumell Bonet; Susana Rodríguez Gonzalez; Francisco Velo Serrano; Manuel Davó Devesa; Héctor Bernabé Jiménez (Universidad de Alicante, 2012)
2011 marks the first century of the Spanish military aviation, since 1911 is considered its initial year. The objective of this study is to present the first military nursing professionals that carried out their jobs in the health care of the early Spanish Air Force. The development of this study presents a basic historiographic story, linking the evolutions of health care and the Spanish military aviation, and covering the early professionals of nursing in aviation units back in 1928.